2017
DOI: 10.1371/journal.pone.0186723
|View full text |Cite|
|
Sign up to set email alerts
|

Association of birth weight with corneal power in early adolescence: Results from the National Health and Nutrition Examination Survey (NHANES) 1999–2008

Abstract: PurposeTo analyze the effect of birth weight on ocular morphology, refraction and visual function in early adolescents aged 12–15 years.Material and methodsWe conducted a secondary data analysis using the public use files from the National Health and Nutrition Examination Survey of the period from 1999 to 2008. Study participants aged 12 to 15 years were included with data on birth weight and ophthalmic parameters including presenting distance visual acuity, objective refraction and keratometry. Visual acuity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 33 publications
0
25
0
1
Order By: Relevance
“…The curvature of the cornea is also thought to be linked with birthweight. 17 Similarly, a twin study investigating 1498 participants aged between 5 to 80 years found that low birthweight was associated with a more curved cornea. 18 It is possible that these associations may also contribute to alterations in corneal aberrations in former preterm infants.…”
Section: Discussionmentioning
confidence: 98%
“…The curvature of the cornea is also thought to be linked with birthweight. 17 Similarly, a twin study investigating 1498 participants aged between 5 to 80 years found that low birthweight was associated with a more curved cornea. 18 It is possible that these associations may also contribute to alterations in corneal aberrations in former preterm infants.…”
Section: Discussionmentioning
confidence: 98%
“…Myopia is more common in children with extremely low birth weight (BW), either with or without retinopathy of prematurity [6,7], although an increased prevalence of hyperopia and astigmatism has also been reported [8,9]. The ocular structure primarily responsible for causing myopia in individuals with extremely low BW is unclear, since both corneal curvature and axial length have been reported to differ in preterm vs. full-term-born infants, and there is evidence suggesting some of these differences may resolve during childhood [10][11][12]. However, few epidemiological studies have assessed the relationship between refractive error and BW within the normal range, either for adult or child samples.…”
Section: Introductionmentioning
confidence: 99%
“…In both studies, statistical support for the association was weak. No association between BW and refractive error was found in 12 to 15 year-old adolescent participants in the US National Health and Nutrition Examination Survey (NHANES), although BW was associated with corneal curvature [11]. In adult participants from the population-based 1958 British Birth Cohort [15], myopia was associated with lower BW for gestational age (OR=0.90, P<0.05) and in the populationbased Gutenberg Health Study [16], refractive error was -0.017 D (95% CI -0.011 to -0.023; P<0.001) more myopic per standard deviation reduction in BW.…”
Section: Introductionmentioning
confidence: 99%
“…L ow birth weight is an indicator of impaired prenatal growth or preterm birth and is a risk factor for systemic comorbidities in adulthood such as arterial hypertension and diabetes. 1,2 Recent reports 3,4 show that altered prenatal growth development affects ocular morphology in childhood and adolescence. However, few population-based studies have reported associations between low birth weight and corneal curvature, 3 corneal power, 4 and axial length 3 in childhood and adolescence.…”
mentioning
confidence: 99%